Frentizole derivatives with mTOR inhibiting and senomorphic properties - Chrienova, Zofia; Rysanek, David; Novak, Josef; Vasicova, Pavla; Oleksak, Patrik; Andrys, Rudolf; Skarka, Adam; Dumanovic, Jelena; Milovanovic, Zoran; Jacevic, Vesna; Chvojkova, Marketa; Holubova, Kristina; et al. (Biomedicine & pharmacotherapy, 2023)
Frentizole is immunosuppressive drug with low acute toxicity and lifespan-prolonging effect. Recently, frentizole ́s potential to disrupt toxic amyloid β (Aβ) - Aβ-binding alcohol dehydrogenase (ABAD) interaction in mitochondria in Alzheimer ́s brains has been revealed. Another broadly studied drug with anti-aging and immunosuppressive properties is an mTOR inhibitor - rapamycin. Since we do not yet precisely know what is behind the lifespan-prolonging effect of rapamycin and frentizole, whether it is the ability to inhibit the mTOR signaling pathway, reduction in mitochondrial toxicity, immunosuppressive effect, or a combination of all of them, we have decided within our previous work to dock the entire in-house library of almost 240 Aβ-ABAD modulators into the FKBP-rapamycin-binding (FRB) domain of mTOR in order to interlink mTOR-centric and mitochondrial free radical-centric theories of aging and thus to increase the chances of success. Based on the results of the docking study, molecular dynamic simulation and MM-PBSA calculations, we have selected nine frentizole-like compounds (1 - 9). Subsequently, we have determined their real physical-chemical properties (logP, logD, pKa and solubility in water and buffer), cytotoxic/cytostatic, mTOR inhibitory, and in vitro anti-senescence (senolytic and senomorphic) effects. Finally, the three best candidates (4, 8, and 9) have been forwarded for in vivo safety studies to assess their acute toxicity and pharmacokinetic properties. Based on obtained results, only compound 4 demonstrated the best results within in vitro testing, the ability to cross the blood-brain barrier and the lowest acute toxicity (LD50 in male mice 559 mg/kg; LD50 in female mice 575 mg/kg).
Keywords: Animals; Female; Amyloid beta-Peptides; TOR Serine-Threonine Kinases; ženské pohlaví; amyloidní beta-protein; Mice; Immunosuppressive Agents; myši; Male; Sirolimus; Alzheimer Disease; Alzheimerova nemoc; sirolimus; zvířata; mužské pohlaví; léky proti stárnutí; TOR serin-threoninkinasy; Senotherapeutics; imunosupresiva